Defining and measuring the relevance of criteria for the evaluation of the inflow of goods in city centers - Mladen Jardas; Ana Perić Hadžić; Edvard Tijan (Logistics, 2021)
The aim of this paper is to define and measure the relevance of the criteria for the evaluation of the inflow of goods in city centers, in order to improve delivery activities within city centers. The development of the city center leads to the grouping of numerous business operators, which results in the increase of the quantity of goods entering the city center, causing additional traffic congestion, higher levels of noise and emissions of harmful gases. In the long term, this leads to major dissatisfaction with the quality of life among city residents. Therefore, the planning of goods delivery must be in line with the sustainable development of city logistics, while at the same time considering the interests of relevant stakeholders. However, in the existing literature the criteria for evaluating delivery flows have not been comprehensively identified or evaluated by the stakeholders of city centers. In order to fill the research gap, the authors have defined four groups of criteria: technical-technological, economic-financial, organizational and social criteria. To determine the relevance of these criteria, it was necessary to use the questionnaire method to collect data from the stakeholder groups defined by the literature review. Regarding the relevant stakeholders (carriers, delivery recipients, residents and urban policy makers), the results have pointed out that the technical-technological and organizational criteria groups are considered the most relevant by the stakeholders regarding the inflow of goods in city centers.
Keywords: 650; city logistics; delivery flows; interest groups; evaluation criteria